Commentary discourse on the methods of science - Velasco, Jose R.; Alejar, Arcelia A.; Dionisio-Sese, Maribel L. (2000)
The paper presents a bird's-eye view of the development of scientific methods. Compared with the relatively flexible methods used in natural history studies, the experimental method is less flexible because conditions in the trials are more rigidly controlled. However, increased precision in the experimental method has enabled the physical sciences to advance tremendously, making major contributions to theory and the practical arts. Limitations of the methods are also pointed out. The essence of scientific research is cursorily presented.
Keywords: Academic discourse; Research methodology; Scientific experimentation